The rates of visual field progression in glaucoma and its clinical importance - Palakkamanil,Mathew M. (2022)
ABSTRACT The rate of visual field progression is an essential factor in determining risk of visual disability or blindness in glaucoma patients. Knowledge of the rate of progression of a particular patient, in combination with an estimation of their longevity and other clinical factors, allows clinicians to optimize management by providing appropriately aggressive treatment. Despite decades of research on the treatment of glaucoma, the natural history of glaucomatous visual field progression in untreated and treated patients remains unclear. The purpose of this review is to provide a comprehensive summary of the literature surrounding the rate of visual field progression in glaucoma. Most of the available data pertains to primary open angle glaucoma, but we will also review progression rates in other subtypes of open angle glaucoma, such as pseudoexfoliative glaucoma and normal tension glaucoma, as well as in primary angle closure glaucoma. Specifically, we will cover methods to identify rates of progression, rates of progression in treated versus untreated patients, factors that may influence progression, and lastly, suggest some parameters that might help clinicians in determining acceptable rates of visual field deterioration in patients with glaucoma.